Magnetic resonance of semiconductors and their nanostructures : basic and advanced applications /: basic and advanced applications. (2017) - Baranov, Pavel G; Bardeleben, H. J. von; Jelezko, Fedor; Wrachtrup, Jörg
No abstract available